2002
DOI: 10.1348/135910702320645390
|View full text |Cite
|
Sign up to set email alerts
|

Optimism and adaptation to chronic disease: The role of optimism in relation to self‐care options of type 1 diabetes mellitus, rheumatoid arthritis and multiple sclerosis

Abstract: Objectives: To determine the role of optimistic beliefs in adaptation processes of three chronic diseases different in controllability by self‐care. It was expected that optimism towards the future would relate to adaptation independently of the controllability of disease. Optimism regarding one's coping ability should be beneficial in controllable diseases. Unrealistic optimism was expected to be beneficial in uncontrollable disease. Design: The cross‐sectional design involved 104 patients with type 1 diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 63 publications
8
102
1
4
Order By: Relevance
“…Earlier research showed that there are at least three different concepts, namely positive outcome expectancies, positive efficacy expectancies, and optimistic bias (Schwarzer, 1994;Fournier et al, 1999Fournier et al, , 2002. In the present study, it is expected that the three types of optimistic beliefs will react differently to chronic disease, depending on their differential sensitivity to disease-related stressors.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Earlier research showed that there are at least three different concepts, namely positive outcome expectancies, positive efficacy expectancies, and optimistic bias (Schwarzer, 1994;Fournier et al, 1999Fournier et al, , 2002. In the present study, it is expected that the three types of optimistic beliefs will react differently to chronic disease, depending on their differential sensitivity to disease-related stressors.…”
mentioning
confidence: 62%
“…In the regression analyses both samples will be analyzed together, controlling for perceived control of illness indicated by a dummy variable of the Chance LOC (with 1 indicating IDDM and 0 indicating MS). The Chance LOC was preferred as an indicator of perceived controllability of illness as it is primarily determined by environmental factors in contrast to both other scales which tend to be dispositional variables depending on genetic factors (Johansson et al, 2001;Fournier et al, 2002).…”
Section: Controllability Of Chronic Diseasementioning
confidence: 99%
“…Desde la visión positiva de la salud se ha estudiado y definido el optimismo como la preferencia de una persona a ser motivada por la creencia que los resultados deseados son fácilmente alcanzables y a su vez se ha relacionado con efectos positivos sobre la salud psicológica y física (Brannon & Feist, 2001); así mismo el optimismo ha sido identificado como factor determinante de la calidad de vida tanto en personas enfermas como personas sanas (Fournier, Ridder, & Bensing, 2002;Gordon, Feldman, Crase, & Schoen, 2002). La importancia y relación existente entre optimismo y salud es estrecha, se considera que las personas optimistas son menos vulnerables a adquirir enfermedades físicas, tienen mejor funcionamiento del sistema inmunológico y menor tasa de mortalidad (Remor, Amorós, & Carrobles, 2006).…”
Section: Introductionunclassified
“…Chronic pain in RA is considered as an uncontrollable stressor [1], which implies low ability to determine its course and outcomes by self-care options [9]. Therefore emotion-focused coping rather than problem-focused coping might be more effective and beneficial for this group of patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with positive outcome expectancies are more engaged in taking up health-oriented behaviours, even if this involves dealing with obstacles and challenges [9]. The significance of optimism in the experience of pain is due to its influence on coping strategies.…”
Section: Discussionmentioning
confidence: 99%